Outcomes from a pilot online Acceptance and Commitment Therapy program for dementia family caregivers. (14th July 2022) - Fauth, Elizabeth B.; Novak, Josh R.; Levin, Michael E.
Abstract: Objectives: Psychosocial and cognitive-behavioral dementia caregiver interventions are effective, yet accessing counselor/therapist-led programs can be costly and difficult. Face-to-face therapist-led Acceptance and Commitment Therapy (ACT) is highly effective in dementia caregivers, as established by two different randomized control trials. The current study evaluates a pilot ACT for Caregivers program, which is a community-based, self-guided, online adaptation of ACT. Method: Participants ( N = 51; M age =66.0 S. D =11.7, 80% women) completed 10 self-guided sessions teaching ACT, along with accessing an online dementia education library. Results: Repeated measures ANOVA from pre-, posttest, and 4-week follow-up demonstrated decreased depressive symptoms, burden, and stress reactions to behavioral symptoms, and increased positive aspects of caregiving and quality of life. ACT-specific measures improved, with decreases in cognitive fusion and psychological inflexibility (AAQ-II), and improvements in living according to personal values (ValuingProgress increased; ValuingObstruction decreased). All outcomes were statistically significant (at p < .01) and sustained over 4-week follow-up. Although this was a non-clinical sample, the program demonstrated clinical significance, as average depressive symptoms were at the clinical cutoff at baseline, but one standard deviation below clinical cut-off at post-test and 4-week followup. Use of education materials was low (29% of participants used these, albeit rating them helpful), suggesting that ACT likely contributed more to overall improvements. Conclusion: The online ACT for Caregivers pilot program offers an empirically supported translation of traditional ACT, improving accessibility, and affordability for family dementia caregivers.